The Critical Need for an Anticapitalist and Intersectional Paradigm for Ecological Thinking - Rodilosso, Ermelinda (Scenari, 2023)
In this paper I intend to outline the main features of Nancy Fraser’s ecological thinking, drawing attention to the most cutting-edge aspects of her elaboration. In particular, I connect the concept of capitalism as an institutionalized social order with the identification of an intersectional ecological framework that can provide an articulated view of the environmental crisis. Indeed, the assumption of an intersectional model is the first step in building a theoretical account that integrates ecological thinking and socio-political dimensions. Before diving into any Marxist investigation on climate change, however, one must ask the age-old question: what is capitalism? By comprehensively answering this query, Fraser confronts us with contradictory and dysfunctional elements that force us to question the existing relationship between capitalism and nature. This reflection raises our awareness about the need to build an account that is counter-hegemonic and oriented toward a radical modification (if not deterioration) of this institutionalized social order.